Phenotypic profile and factors of blood lymphocytes apoptosis induction in patients having diffuse toxic goiter - O. I. Ourazova; Ye. B. Kravets; V. V. Novitsky; A. V. Rogalyova; O. A. Vasilyeva; Yu. V. Nedosekova; S. E. Barmina (Бюллетень сибирской медицины)
Peculiarities of phenotypic structure and factors of apoptosis induction (level of CD95-antigen cell expression, blood serum content of TNF-α ) of peripheral blood lymphocytes in patients with diffusive toxic goiter are discussed in thе article.